Cardiac Imaging and Management of Cardiac Disease in Asymptomatic Renal Transplant Candidates: A Current Update - Lioudaki, Eirini; Androvitsanea, Ariadni; Petrakis, Ioannis; Bakogiannis, Constantinos; Androulakis, Emmanuel (Diagnostics, 2022)
Given the high cardiovascular risk accompanying end-stage kidney disease, it would be of paramount importance for the clinical nephrologist to know which screening method(s) identify high-risk patients and whether screening asymptomatic transplant candidates effectively reduces cardiovascular risk in the perioperative setting as well as in the longer term. Within this review, key studies concerning the above questions are reported and critically analyzed. The lack of unified screening criteria and of a prognostically sufficient screening cardiovascular effect for renal transplant candidates sets the foundation for a personalized patient approach in the near future and highlights the need for well-designed studies to produce robust evidence which will address the above questions.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cardiovascular screening; chronic kidney disease; coronary angiography; end-stage kidney disease; renal transplantation; timing